2000
DOI: 10.1103/physrevb.62.10548
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent melting point depression of nanostructures: Nanocalorimetric measurements

Abstract: The melting behavior of 0.1-10-nm-thick discontinuous indium films formed by evaporation on amorphous silicon nitride is investigated by an ultrasensitive thin-film scanning calorimetry technique. The films consist of ensembles of nanostructures for which the size dependence of the melting temperature and latent heat of fusion are determined. The relationship between the nanostructure radius and the corresponding melting point and latent heat is deduced solely from experimental results ͑i.e., with no assumed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
302
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(322 citation statements)
references
References 34 publications
19
302
0
1
Order By: Relevance
“…For this to be true, the 1789℃ bulk melting point of Pt would have to be depressed to the 900℃ substrate temperature during growth. This could be achieved by a combination of Pt particle size effect 19 and Ga alloying.…”
mentioning
confidence: 99%
“…For this to be true, the 1789℃ bulk melting point of Pt would have to be depressed to the 900℃ substrate temperature during growth. This could be achieved by a combination of Pt particle size effect 19 and Ga alloying.…”
mentioning
confidence: 99%
“…This result indicated that the crystal morphology of the treated sodium selenate was changed from the control sample and The Trivedi Effect ® -Biofield Energy Healing might lead to a new polymorphic form of sodium selenate. The particle sizes d 10 , d 50 , and d 90 values of the treated sample were significantly decreased by 3.40%, 9.75%, and 8.52%, respectively as compared to the control sample. Additionally, the surface area of the treated sample was increased by 5.26% from the control sample.…”
Section: Resultsmentioning
confidence: 77%
“…Interestingly, the latent heat of fusion (∆H) of the treated sodium selenate (96.77 J/g) was lower by 8.01% from the control sample (∆H = 105.2 J/g). Literature demonstrated that decreased particle size depress the latent heat of fusion [50]. As the treated sample has reduced particle size, it has lower latent heat of fusion compared with the control sample.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-calorimetry is a very sensitive calorimetry technique capable of measuring the thermodynamic properties of nano-quantities of materials. The technique has been applied to study phase transformations in thin-film samples with thickness as small as a few nanometers [5,16,54,55,61,82,[94][95][96]. A recently developed scanning AC nano-calorimetry technique can be used to measure heat capacity over a wide range of temperatures (up to 1300 K) and heating rates (from isothermal to 3000 K/s) [22,24,81].…”
Section: Introductionmentioning
confidence: 99%